2004
DOI: 10.1086/422691
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with the C‐Domain of α‐Toxin Prevents Lethal Infection, Localizes Tissue Injury, and Promotes Host Response to Challenge withClostridium perfringens

Abstract: Clostridium perfringens gas gangrene is characterized by rapid tissue destruction, impaired host response, and, often, death. Phospholipase C (alpha -toxin) is the virulence factor most responsible for these pathologies. The present study investigated the efficacy of active immunization with the C-terminal domain of alpha -toxin (Cpa247-370) in a murine model of gas gangrene. Primary end points of the study were survival, progression of infection, and tissue perfusion. Secondary end points, which were based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 26 publications
0
42
1
1
Order By: Relevance
“…Reports on monoclonal antibodies against alpha toxin led to the finding that monoclonal antibodies, which were capable of neutralizing the phospholipase C activity, were not necessarily effective in neutralizing the haemolytic and lethal activities of the toxin in gangrene models (Sato et al, 1989;Logan et al, 1991). The immune response against the C-domain provided protection against challenge with alpha toxin and also against experimental gas gangrene in mice (Stevens et al, 2004).…”
Section: An Overview Of Vaccination Studies Against Necrotic Enteritismentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on monoclonal antibodies against alpha toxin led to the finding that monoclonal antibodies, which were capable of neutralizing the phospholipase C activity, were not necessarily effective in neutralizing the haemolytic and lethal activities of the toxin in gangrene models (Sato et al, 1989;Logan et al, 1991). The immune response against the C-domain provided protection against challenge with alpha toxin and also against experimental gas gangrene in mice (Stevens et al, 2004).…”
Section: An Overview Of Vaccination Studies Against Necrotic Enteritismentioning
confidence: 99%
“…The alpha toxin is the most investigated C. perfringens toxin in terms of vaccine-induced protection, mainly in mouse gangrene models (Stevens et al, 2004;Titball, 2009). The alpha toxin is composed of two domains, which are associated with phospholipase C activity (N-domain) and membrane recognition (C-domain) (Naylor et al, 1998).…”
Section: An Overview Of Vaccination Studies Against Necrotic Enteritismentioning
confidence: 99%
“…Although vaccination offers an alternative approach to antimicrobial drugs in control of the disease, little is known about immunity to NE. However, there is the suggestion that the alpha-toxin, a phospholipase C exoenzyme, is an important immunogen (1,13,21). A recent study showed that alpha-toxin is not essential in the pathogenesis of NE (10).…”
mentioning
confidence: 99%
“…perfringens is the most common cause of gas gangrene, an acute infection associated with traumatic or surgical wounds and characterized by intravascular leukocyte accumulation, thrombosis, and severe myonecrosis (217). A C. perfringens mutant strain with an inactivated plc is unable to produce gas gangrene (218), and immunization with the alpha-toxin C-terminal domain protects mice against experimental gas gangrene induced by C. perfringens (219). Similarly, immunization of guinea pigs with the Clostridium haemolyticum PLC elicits a protective immunity from an intramuscular challenge with 50 LD 50 s of this bacterium (220).…”
Section: Phospholipase Csmentioning
confidence: 99%